Relationship of serum Fetuin-A with metabolic and vascular parameters in patients with prediabetes and type 2 diabetes mellitus - Vera Karamfilova; Iveta Nedeva; Tsvetan Gatev; Antoaneta Gateva; Yavor Assyov; Antonina Gerganova; Dobrin Popov; Tsvetelina Velikova; Zdravko Kamenov (Pensoft Publishers, 2023)
Background: Fetuin-A is a multifunctional liver-derived glycoprotein that is associated with insulin resistance and might play a role in the pathogenesis of prediabetes and type 2 diabetes (T2DM). Objective: This study evaluated the relationship of Fetuin-A with metabolic and vascular parameters in patients with prediabetes and T2DM. Materials and methods: total 120 obese patients were included. They were divided into three groups: group 1 - without carbohydrate disturbances, group 2 - with prediabetes and group 3 - with type 2 diabetes mellitus. Results: Higher Fetuin-A serum levels were observed in patients with prediabetes and T2DM compared to those with normoglycemia. Fetuin-A ≥821 mcg/ml increased the risk for T2DM 32-fold. Additionally, we found positive correlations between Fetuin-A, vibration perception threshold and toe-brachial index and a negative correlation with neuropathy disability score. Conclusion: Fetuin-A could be predictive for incidents of prediabetes and T2DM.